German evidence and consensus‐based (S3) guideline: Vaccination recommendations for the prevention of HPV‐associated lesions. (26th February 2021) - Gross, Gerd E.; Werner, Ricardo N.; Avila Valle, Gabriela L.; Bickel, Markus; Brockmeyer, Norbert H.; Doubek, Klaus; Gallwas, Julia; Gieseking, Friederike; Haase, Heidemarie; Hillemanns, Peter; Ikenberg, Hans; Jongen, Johannes; et al.
Summary: Anogenital and oropharyngeal infections with human papilloma viruses (HPV) are common. Clinically manifest disease may significantly impact quality of life; the treatment of HPV‐associated lesions is associated with a high rate of recurrence and invasive neoplasms, such as cervical, anal, vulvar, penile, and oropharyngeal cancers, which are characterized by significant morbidity and mortality. Vaccination against HPV is an effective and safe measure for the primary prevention of HPV‐associated lesions, but immunization rates are still low in Germany. The present publication is an abridged version of the German evidence and consensus‐based guideline "Vaccination recommendations for the prevention of HPV‐associated lesions", which is available on the website of the German Association of the Scientific Medical Societies (AWMF). On the basis of a systematic review with meta‐analyses, a representative panel developed and agreed upon recommendations for the vaccination of different populations against HPV. In addition, consensus‐based recommendations were developed for specific issues relevant to everyday practice. Based on current evidence and a representative expert consensus, these recommendations are intended to provide guidance in a field in which there is often uncertainty and in which both patients and health care providers are sometimes confronted with controversial and emotionally charged points of view.